Parâmetros nutricionais de ovinos alimentados com dietas contendo associação dos óleos babaçu e girassol - VILELA, Gleice Kelle Silva Marques (2023)
The objective was to evaluate the addition of sunflower oil (OG) and its association with babassu oil (OB) in feedlot sheep on consumption, digestibility and ruminal parameters. Thirty five lambs with an average weight of approximately 16 ± 3.9 kg, male, castrated, crossbred, fed five experimental diets were used: diet without oil (SO); 4.5% OBA; 3.0% OBA and 1.5% OG; 2.25% OB and 2.25% OG; 3.0% OG and 1.5% OB, based on dry matter. The design used was in randomized blocks with five treatments (diets) and seven repetitions (animals). The experimental period was 60 days (10 days of adaptation and 44 days of confinement and six days of data collection). Intake and digestibility of dry matter (DM), organic matter (OM), crude protein (CP), neutral detergent fiber (NDF), non-fiber carbohydrates (NFC), total carbohydrates (CHOT), ether extract ( EE ), as well as ruminal parameters pH, ammoniacal (N-NH3) and recipes for short wheelchairs. There was a quadratic effect (P˂0.05) for intakes of DM, PB, MO, NDF, EE, CHOT, CNF, and EM, ruminal pH, molar concentrations of SCFA, propionate, butyrate, isovaleric, acetate:propionate ratio and interaction treatment x hours of collection only for the isovaleric, and for number of protozoa per log 10/ml. Maximum DM consumption was observed: 894.46g/day; CP:168.51 g/day; MO:845.98 g/day; NDF:386.98 g/day; EE:59.94g/day; CHOT:616.37 g/day; CNF:308.01 g/day and ME: 2.79 g/day, and higher concentrations when added 2.44; 2.16; 2.25; 1.81; 1.86% of sunflower oil for ruminal pH, molar concentrations of propionate, butyrate, isovaleric, acetate:propionate ratio, respectively, and also higher number of protozoa (3.98 per log10/ml). There was no effect (P>0.05) for N-NH3 concentrations. Sunflower and babassu oil can be used in the diets of Dorper x Santa Inês crossbred sheep in finishing in the proportion of 1.5% sunflower oil and 3.0% babassu oil.